Early Identification, Intervention and Management of Post-stroke Spasticity: Expert Consensus Recommendations. (23rd September 2021) - Bavikatte, Ganesh; Subramanian, Ganesh; Ashford, Stephen; Allison, Rhoda; Hicklin, Dawn
Stroke patients with spasticity usually require long-lasting care and interventions but frequently report that outpatient and community treatment is limited, reflecting a significant unmet need in health and social care provision. Rehabilitation and spasticity management services are essential for patient recovery, with improvements in both activity and participation reducing the burden on patients, family and society. Current clinical guidance provides scope for improvements in both post-stroke management and spasticity prevention. However, access to specialist services can be limited and the patient journey does not always match national recommendations. Identification of spasticity and its predictors and lack of subsequent referral to rehabilitation or specialist spasticity services are key issues in the management of post-stroke spasticity. Implementation of a traffic light classification system prioritises patients at an increased risk of spasticity and promotes early and consistent management across the spectrum of primary and secondary care. The proposed system is based on clinical evidence, expert consensus and recent clinical guidelines. It provides simple and straightforward criteria for management, multidisciplinary consultation and referral to specialist spasticity services, with patients allocated by monitoring requirements and a low (green/periodic monitoring), medium (amber/routine referral) or high risk (red/urgent referral) of spasticity.